Linguistic Impoliteness and Interpersonal Positioning in Nigerian Online Political Forum - Taiwo, Rotimi; Akinwotu, Alaba; Kpolugbo, Stella (Linguistik Online, 2021)
Interactional positioning has to do with how people express their attitudes and dispositions to others (stance) and signal how they wish to relate with other participants in the discourse (engagement). These are closely connected with the extent to which impoliteness is expressed in discourse and the resources and strategies employed. This study investigates interactional positioning and impoliteness in two Nigerian political discussion sites, Nairaland Forum and Gistmania. The findings show that bald-on-record and negative impoliteness were predominant in the discussions. The common linguistic expressions of impoliteness were name-calling, vulgarism, cursing, dismissal and sarcasm. Participants also used questions, directives and reader pronouns you and your for face attacks and heightening of the effect of impolite expressions. Self-mentions and attitude markers, especially cognitive verbs, were used to convey feelings and attitudes towards other participants within and outside the discussion. The study concludes that impoliteness thrives in political debates online because of the uninhibited context, which gives freedom to participants to deliberately inject invective language in order to set the emotional temperature in the discussion and cause disaffection among the participants and the group they represent.